Effects of 9‐cis retinoic acid on human homeobox gene NKX3.1 expression in prostate cancer cell line LNCaP - Jiang, An‐Li; Zhang, Peng‐Ju; Chen, Wei‐Wen; Liu, Wen‐Wen; Yu, Chun‐Xiao; Hu, Xiao‐Yan; Zhang, Xiao‐Qian; Zhang, Jian‐Ye (Asian journal of andrology, 2006)
Aim: To study the regulatory effects of 9‐cis retinoic acid (RA) on the expression of human homeobox gene NKX3.1 in prostate cancer cell line LNCaP. Methods: Flow cytometry, reverse transcriptase polymerase chain reaction and Western blotting were performed to evaluate the effects of 9‐cis RA on NKX3.1 expression and cell cycle of LNCaP cells. To identify a regulatory region within the NKX3.1 promoter contributing to the regulation induced by 9‐cis RA, we have constructed an NKX3.1 promoter‐reporter plasmid, pGL3‐1040bp, and its 5′‐deletion mutants, which were transfected into LNCaP cells with treatment of 9‐cis RA in indicated concentrations. Results: With the treatment of 9‐cis RA, the NKX3.1 promoter activity was increased in reporter gene assay and NKX3.1 expression was enhanced at both mRNA and protein levels in LNCaP cells. We found that the region between ‐936 and ‐921 in the upstream of NKX3.1 gene involved the inducible regulation by 9‐cis RA treatment. In flow cytometry, 9‐cis RA treatment caused accumulation of cells in the G1 phase of the cell cycle and a fewer cells pass through to G2/M. Conclusion: Our results demonstrated that 9‐cis RA as a differentiating agent can arrest prostate cancer cells in G1 phase and reduce cell mitosis, and upregulate the expression of human homeobox gene NKX3.1, which is thought to play an important role in prostate differentiation and to act as a tumor suppressor gene in the prostate.